2010
DOI: 10.1111/j.1745-4573.2010.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Profile and Sensory Characteristics of Dry‐cured Loins as Affected by Feeding Level in the Period Previous to the Late Fattening Phase and by Rearing System of Iberian Pigs

Abstract: The effect of a moderate feed restriction (50 g feed/kg LW 0.75 [low feeding level, L] versus 70 g feed/kg LW 0.75 [high feeding level, H]) during the period previous to the late fattening phase on chemical composition, volatile profile and sensory quality of Iberian dry-cured loins from animals reared in free range (FR) or in confinement (C) along the fattening phase was studied. Total tocopherol, total free amino acid and ammonia contents of dry-cured loins from pigs FRL and FRH were higher (P < 0.05) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…For example, Hersleth, Lengard, Verbeke, Guerrero, and Næs () showed that depending on the consumer segment (age and gender), the reactions to process or product innovations are significantly different, including when the salt content varies. The judgments of the panel are also a function of the other elements that change in the products (drying time, origin of the meat, indoor/outdoor animal feeding (Soto et al., )). In other words, for the technological properties of PMPs, the interaction between consumer perception and the salt content of the product is linked to a set of general parameters of overall meat quality (Hung, Verbeke, & de Kok, ).…”
Section: Societal Perception Of Salt In Processed Meatmentioning
confidence: 99%
“…For example, Hersleth, Lengard, Verbeke, Guerrero, and Næs () showed that depending on the consumer segment (age and gender), the reactions to process or product innovations are significantly different, including when the salt content varies. The judgments of the panel are also a function of the other elements that change in the products (drying time, origin of the meat, indoor/outdoor animal feeding (Soto et al., )). In other words, for the technological properties of PMPs, the interaction between consumer perception and the salt content of the product is linked to a set of general parameters of overall meat quality (Hung, Verbeke, & de Kok, ).…”
Section: Societal Perception Of Salt In Processed Meatmentioning
confidence: 99%
“…Lipids markedly affect the quality of dry-cured hams and other meat products not only because of their importance in oxidation and flavor development (Soto et al, 2010) but also because the physical characteristics of fat affect technological properties (Houben & Krol, 1983;Hugo & Roodt, 2007) and final acceptability (Fernández, Mourot, Lebret, Gilbert, & Monin, 2000). Lean swine genotypes are prone to produce soft, oily and floppy fat (Wood, 1984) with dramatic undesirable consequences in salting, flavor development and consistency of drycured meat products (Gandemer, 2002;Isabel et al, 2003;Maw, Fowler, Hamilton, & Petchey, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…They conclude that the most important volatile compounds in terms of basic contribution to cured-ham odor and taste are 3-methylbutanal, hexanol, limonene, 3-methylbutanol, hexanal, 2-nonanone and benzaldehyde for Spanish dry-cured hams [38]. In addition, these cured-ham relevant volatiles were found as well in cured loins [4][5][6]. In the present study, four of these compounds were investigated, and 3-methylbutanal, nonanone and benzaldehyde can be found in the models described above (Eqs.…”
Section: Sensory Analysismentioning
confidence: 96%
“…Raw material quality, processing parameters, curing ingredients, microbiota as well as other intrinsic and extrinsic factors influence the quality of cured ham or loin. Time and temperature profiles during ripening and storage particularly affect the profile of volatile compounds of cured hams and loins due to proteolytic, lipolytic and peptidolytic degradation processes in the cured meat matrix [4][5][6][7][8]. Traditional slowly matured dry-cured hams are mainly ripened at 15-18 °C, and temperatures around 24 °C are used for quickly ripened hams [1].…”
Section: Introductionmentioning
confidence: 99%